PENGENDALIAN KAS PADA PT. KUKAR MANDIRI SHIPYARD - -, Varianto - (EKONOMIA, 2014)
In this reformation era, budgeting is essential for surveillance work (controlling). Budget has two important roles within the company. On the one hand, the budget serves as a tool for planning, budgets and on the other hand acts as a short-term controllers for an organization. This study was conducted at PT. Kukar Mandiri Shipyard which is a company engaged in the services of shipbuilding and ship repair. Cash on this company sometimes still exaggerated and sometimes shortcomings, this is because the predictions of payment from the owner of the vessel often miss the due and sometimes uncertain sales outlook so if it misses, the prediction of sales purchase will also slip and receipt of working capital, which has not made sure that the budget is not yet effective.The problem in this research is